2014
DOI: 10.1177/1535370214547157
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholyl lysophosphatidylethanolamide inhibits cholestasis- and hypoxia-induced apoptosis by upregulating antiapoptosis proteins

Abstract: An increase of toxic bile acids such as glycochenodeoxycholic acid occurs during warm ischemia reperfusion causing cholestasis and damage in hepatocytes and intrahepatic biliary epithelial cells. We aim to test antiapoptosis effects of ursodeoxycholyl lysophosphatidylethanolamide under cholestatic induction by glycochenodeoxycholic acid treatment of mouse hepatocytes and hypoxia induction by cobalt chloride treatment of intrahepatic biliary epithelial cancer Mz-ChA-1cell line. Such treatments caused marked inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The effect of UDCA on apoptosis inhibition has been reportedly mediated by the upregulation of various anti-apoptotic proteins, such as FLICE-inhibitory protein, myeloid leukaemia sequence-1 protein, and cellular inhibitor of apoptosis-2 protein. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The effect of UDCA on apoptosis inhibition has been reportedly mediated by the upregulation of various anti-apoptotic proteins, such as FLICE-inhibitory protein, myeloid leukaemia sequence-1 protein, and cellular inhibitor of apoptosis-2 protein. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In cholestasis, hydrophilic BAs decrease; therefore, protecting proteins such as NFκB, cFLIP, CIAP2, and MCL‐1 are inhibited, decreasing bile flow and cholesterol solubility furthermore increasing the NOSs. Alterations in lipid metabolism contribute to the pathogenesis and progression of cholestatic liver disease . Meanwhile, cholestasis enhances the expression of various transporters, such as BSEP, ABCB4, SHP, ABCA1, and the heterodimer ABCG5/ABCG8, which increase the excretion of cholesterol from the liver to the serum, affecting the bile flow, increasing toxic BAs concentration, rising inflammation, and liver damage (Figure ) …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in an HepG2 and primary hepatocyte cellular model, the UDCA‐lysophosphatidylethanolamide (UDCA‐LPE) complex is effective in apoptosis inhibition, affecting both intrinsic and extrinsic pathways, inducing survival signals such as nuclear factor kappa‐light‐chain‐enhancer of activated B cells in part by accumulation of antiapoptotic cellular FLICE‐like inhibitory protein (cFLIP), cellular inhibitor of apoptosis 2 (CIAP2), and myeloid cell leukemia sequence 1 (Mcl‐1); moreover UDCA‐LPE inhibits the proteasomal degradation of Mcl‐1 via phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) which inhibits downstream Glycogen synthase kinase‐3 alpha and beta (GSK3α/β) signaling pathways, also by the activation of stearoyl‐CoA desaturase‐1 (SCD‐1), an enzyme that converts saturated fatty acids to monosaturated fatty acids, being involved in alterations of fatty acid composition . On the other hand, Akiyama et al.…”
Section: Bile Acidsmentioning
confidence: 99%
“…When the myocardium is deprived of blood, a process involving ischemia, infarction and myocardial remodeling is initiated that leads to myocardial hypoxia (Lee et al, 2000). Evidence from several studies indicated that hypoxia can trigger apoptosis in cardiomyocytes (Sellinger et al, 2015;Yan et al, 2014). Our previous studies showed that long-term intermittent hypoxia could result in eccentric cardiac hypertrophy in rats (Chen et al, 2007) and induce both mitochondrial-dependent apoptotic and Fas death receptor-dependent apoptotic pathways in rat hearts (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 96%